1991
DOI: 10.1007/bf01065321
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation exposure to 1,3-dichloropropene in the Dutch flower-bulb culture. Part II. Biological monitoring by measurement of urinary excretion of two mercapturic acid metabolites

Abstract: A biological monitoring study was carried out in the Dutch flower-bulb culture to determine the relationship between respiratory occupational exposure to Z- and E-1,3-dichloropropene (Z- and E-DCP) and urinary excretion of two mercapturic acid metabolites, N-acetyl-S-(Z- and E-3-chloropropenyl-2)-L- cysteine (Z- and E-DCP-MA). Urinary excretion of Z- and E-DCP-MA, either based on excretion rates or on creatinine excretion, followed first order elimination kinetics after exposure. Urinary half-lives of eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…These data are in good agreement with the results of Van Welie et al 2. The correlation between the 8 hour TWA air concentration of cis -DCP and the concentration of cis -DCP-MA in urine, found by these investigators were r =0.71 in end of shift urine samples and r =0.94 in 24 hour urine samples.…”
Section: Population and Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…These data are in good agreement with the results of Van Welie et al 2. The correlation between the 8 hour TWA air concentration of cis -DCP and the concentration of cis -DCP-MA in urine, found by these investigators were r =0.71 in end of shift urine samples and r =0.94 in 24 hour urine samples.…”
Section: Population and Methodssupporting
confidence: 92%
“…2 Brouwer et al 3 reported that 8 hour time weighted average (TWA) exposures to cis/trans -DCP ranged from 1.9 to 18.9 mg/m 3 . The Dutch OEL of 5 mg/m 3 (1 ppm) was exceeded during 30% of the observed working days.…”
mentioning
confidence: 99%
“…Therefore, though urinary MAs are frequently used as biomarkers of internal dose, they are sometimes also classified as biomarker of effect [22]. Several recent and older examples of MAs used in the BM of human exposure or in biotransformation studies are: N-acetyl-S-(9,10-dihydro-9-hydroxy-10-phenanthryl)-L-cysteine, which originates from a polycyclic aromatic hydrocarbon, phenanthrene, present in cigarette smoke [23], four structurally different mercapturates derived from the herbicides atrazine, acetochlor, metolachlor, and alachlor [24], S-acetamidomethylmercapturic acid, in response to exposure to the industrial solvent N,N-dimethylacetamide [25], N-acetyl-S-(p-chloro- phenylcarbamoyl)cysteine, derives from the anticancer agent sulofenur [26], phenyl mercapturic acid, in response to benzene exposure in industry [27], 3,4-dihydroxybutylmercapturic acid as an environmental and biological monitoring indicator of non-occupational exposure to 1,3-dichloropropene [28], 3-chloro-2-hydroxypropylmercapturic acid and allylmercapturic acid as urinary biomarkers of human exposure to allyl chloride [29], and N-acetyl-S-(Z-and E-3-chloropropenyl-2)-L-cysteine as a biomarker for agricultural soil fumigant 1,3-dichloropropene [30]. In the first part of the studies summarized in this Review, attention is paid to MA derivatives of volatile anesthetics in humans, and whether they are applicable as biomarkers of effect.…”
Section: Mercapturic Acids: Potential Biomarkers Of Effectmentioning
confidence: 99%
“…The mercapturic acid conjugate of 1,3-D has also been identified in the urine of human subjects exposed to mixed isomer vapors of 1,3-D under field application or laboratory conditions and has been utilized as a biomonitor of 1,3-D exposure (Kezic et al, 1996;Osterloh and Feldman, 1993;Osterloh et al, 1984;van Welie et al, 1991;Waechter et al, 1992). Consistent with the earlier rat data, Waechter et al (1992) found that humans excrete approximately 45% and 14% of absorbed cis-and trans-isomers of 1,3-dichloropropene, respectively, as the cis-and transmercapturates, a 3.2:1 ratio.…”
Section: Absorption Distribution Metabolism and Excretionmentioning
confidence: 99%
“…Based upon these data, it has been proposed that 1,3dichloropropene is primarily metabolized in rats and mice, and humans, by conjugation with glutathione and by hydrolysis of the 3-position chlorine (Bartels et al, 2004;Dietz et al, 1984;Fisher and Kilgore, 1988a;Hutson et al, 1971;IPCS, 1993;Onkenhout et al, 1986;Osterloh et al, 1984;van Welie et al, 1991;Waechter et al, 1992). The end-product of the latter pathway is CO 2 .…”
Section: Absorption Distribution Metabolism and Excretionmentioning
confidence: 99%